Mother's single parenting in overseas contract workers' families of San Pedro, San Jose, Antique. - Quanico, Lumen Marie Rose C.
This research deals with the practices and variable circumstances in single-parent families. Interview with the mother and child respondents was instrumental to gather data needed for the study. The study was limited only to wives and children of OCW's who were left at home. , Family background of respondents was being considered as it is one of the variable circumstances in the conduct of the study. Activities of single-parent households include communication between husband and wife, financial support and their children's schooling. On the part of the children, communication with father abroad, their school actvities, activities within and outside the home and problems and expectations were also taken into consideration.